Synchronous childhood T-lymphoblastic lymphoma and B-cell precursor acute lymphoblastic leukemia associated with constitutional MMR deficiency syndrome –a case report - Bulsa, Joanna; Pastorczak, Agata Karolina; Taha, Joanna; Mlynarski, Wojciech; Sędek, Łukasz; Szczepanski, Tomasz (Frontiers in Oncology, 2025)
We present a four-year-old girl with synchronous T-cell lymphoblastic lymphoma (T-LBL) and B-cell precursor acute lymphoblastic leukemia (BCP-ALL).Development of two lymphoid malignancies arising from completely different cell lineages was confirmed by molecular tests. The cause of cancerogenesis in this patient was a genetic predisposition resulting from mismatch repair deficiency syndrome (CMMRD). Herein, we present the fatal course of the disorder, challenging treatment decisions and need for special approach to the patients with CMMRD-associated malignant proliferation.